Effect of Steaming on Nutrients Content of Flaxseed as a Feed Ingredients - Ayu Damayanti; Osfar Sjofjan (Indonesian Journal of Applied Research (IJAR), 2022)
This study aims to find out the effect of steaming on the content of feed substances contained in flaxseed as animal feed. Flaxseed (Linum usitatissimum) is a cereal plant that has high content of protein, energy, and fat, but flaxseed also contain antinutrient substances, namely tannins and phytic acid that can be inhibit the absorption of feed substances. Antinutrients can be decreased by the steaming method. The research material is flaxseed. The study used laboratory experimental with a complete random design (CRD), 4 treatment and 5 replicantions, covering treatment: P0 = Flaxseed without treatment, P1 = Flaxseed steamed for 10 minutes, P2 = Flaxseed steamed for 20 minutes, P3 = Flaxseed steamed for 30 minutes. The observed variables are feed substances dry matter, crude protein, crude fiber, crude fat, ash, gross energy, NDF, ADF, tannins and phytic acid. The analysis used analysis of variance (ANOVA) and Duncan’s Multiple Range Test. The results showed that the treatment had no significant effect (P>0.05) on the dry matter, but had a very significant effect (P<0.01) on crude protein, crude fiber, crude fat, ash, gross energy, NDF, ADF, tannin and phytic acid. It can be concluded that the treatment can decreased feed substances including dry matter, crude protein, crude fat, ash, gross energy, NDF, ADF, tannins and phytic acid, but cannot decreased crude fiber. The best treatment was the steaming flaxseed for 30 minutes.